Tyrosine phosphorylation and morphological transformation induced by four vanadium compounds on MC3T3E1 cells - Salice C., Viviana (1999)
The present study was performed to determine the phosphotyrosine-protein levels induced by insulin and by four vanadium derivatives in MC3T3E1 osteoblast-like cells. We have also attempted to associate these patterns with the vanadium-induced growth and morphological changes of such cells. Vanadate (Vi), vanadyl (VO), bis(maltolato)oxovanadium (IV) (BMOV) and bis(maltolato)dioxovanadium (V) (BMV) stimulate cell growth in a narrow range of concentration, but are also inhibitors for the cells at high concentrations. Vanadium-treated cells displayed clear changes in their morphology after overnight incubation. However, BMV was the least cytotoxic and the weakest inducer of morphological changes. All the compounds promote the phosphorylation of tyrosine residues in several proteins. This effect was more pronounced at low than at high doses. At low doses (10 μM), BMV showed a phosphorylation pattern similar to that of insulin, while Vi, VO and BMOV induced strong phosphorylation of cell proteins. The present findings suggest that the vanadium-induced growth regulation and morphological changes in MC3T3E1 osteoblast-like cells are associated with the ability of these agents to increase the phosphotyrosine protein levels and to inhibit phosphotyrosine phosphatases. These properties are dependent on the oxidation state as well as on the organic ligand which coordinates the vanadium atom.